Ograniczenie działalności telekomunikacyjnej w stanie wojennym i stanie wyjątkowym - Kłusek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Telecommunications activity is apeculiar kind of economic activity. In specific situations, this activity might be subject to limitation. An example of such situations are the circumstances regulated in chapter XI of Polish Constitution, in which the freedom of carrying out telecommunications operations might be limited. This article consists of the description of the types of telecommunications activity and the regulations and laws governing martial law and the state of emergency — which allow the limitation on telecommunications activity.
Keywords: stan wojenny; stan wyjątkowy; telekomunikacja; ograniczenia; rodzaje stanów nadzwyczajnych